The Effect of Motivation and Leadership on Performance Through Productive Behavior - ., Muhdar; ., Bagus; ., Supardi (International Journal of Social Science and Business, 2018)
This study is intended to analyze the influence of motivation and leadership on performance through productive behavior of case studies on Civil Servants (PNS) teachers in Kalibaru State Vocational School. The type of data used is primary data, obtained by interviewing and distributing questionnaires to the population of all Civil Servants teachers in the Kalibaru State Vocational School in amount 38 people. By using regression analysis, the results are obtained: (1). Motivation has a positive and significant influence on productive behavior, (2). Leadership has a positive and significant influence on performance, (3). Motivation has a positive and significant effect on performance through productive behavior, (4). Leadership has an influence on the performance of PNS teachers in Kalibaru State Vocational School, and (5). Productive behavior has an influence on the performance of PNS teachers in Kalibaru State Vocational School. From the results of the study it is expected that schools and principals pay more attention to and improve services to PNS teachers in motivating and leading teachers and providing positive behavior so that PNS teachers can work well, responsibly, comfortably and are able to improve school goals in accordance with the school's vision and mission